Analysis of discrimination on the basis of sexual orientation in the workplace - Tebele, Stephen Maloko (My University, 2013)
Like other forms of prohibited discriminations, discrimination on the basis of sexual orientation has become an area of concern in the workplace. The law prohibits discrimination in whatever form and declares it unlawful to discriminate people on the basis of sexual orientation. In this work, South African anti- discrimination provisions on the basis of sexual orientation will be emphasized, whereas foreign countries will only be referred to for the sake of comparative analysis. Discrimination of lesbian, gay, bisexual, transsexual and homosexual people (LGBTH) in the workplace is manifested by harassment and constructive dismissal through homophobia. Homophobia is a psychological concept which refers to the hatred of people after declaring their gay, lesbian or homosexual identities. This study reveals homophobic practices towards homosexuals as if they are not beneficiaries of contemporary democratic laws and dividends of democracy enshrined in Chapter 2 of the RSA Constitution of 1996 and Chapter 2 of the Employment Equity Act (EEA) 55 of 1998. To this, the research revealed an interesting corroboration in section 9(4) of the RSA Constitution of 1996, and section 6(1) of the EEA 55 of 1998, which provide that no person may unfairly discriminate another on the grounds of sexual orientation. The study has also revealed that among others, employment rights of people in South Africa and in foreign countries are being violated on the basis of sexual orientation. In most case laws, people who disclosed to their employers, that their gender identities are different to what was expected as straight genders and those who informed their employers about their intentions to undergo sex change surgeries are being hired and fired. The study also proved a point that when it comes to sexual orientation exclusion and discrimination, the same vulnerable groups of gays and lesbians are as well caught up in practices of sodomy and sexual harassments. Therefore, the remedies suggested by this research will also apply to everyone including gays and lesbians. To avoid controversy and issues, statutes and decided court cases have been stated as they are, in chapter 4 of this research, for the sake of comparative analysis in order to unravel the existing state of affairs through approaches from different jurisdictions.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2013
Keywords: Employment discrimination; Equal opportunity in employment; Discrimination in employment -- Law and legislation -- South Africa; Sex discrimination in employment